2021
DOI: 10.3389/fpsyt.2021.750033
|View full text |Cite
|
Sign up to set email alerts
|

Sexuality in Ultra-High Risk for Psychosis and First-Episode Psychosis. A Systematic Review of Literature

Abstract: A considerable body of literature reports that individuals with psychotic disorders often suffer from sexual dysfunctions (SDs), with these representing a major unmet need. Long-term antipsychotic drug treatment may be the main cause for SDs in psychotic patients, through a plethora of different mechanisms, including prolactin dyscrasia, histamine-mediated sedation, and serotonin-induced sexual demotivation. However, a few pieces of evidence treat sexuality in patients at risk or the onset of psychosis. For th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 93 publications
0
4
0
Order By: Relevance
“…In men with diabetes and depression, a significantly higher prevalence of ED is observed [ 60 , 134 ], with depressive symptoms showing an independent and positive association with the severity of ED [ 135 ]. Moreover, it has been demonstrated that young people in the early stages of psychosis have higher rates of ED [ 136 ] and that men suffering from bipolar disorder and post-traumatic stress disorder may also have a higher risk of ED [ 137 , 138 ], not associated with the use of psychotropic medications.…”
Section: Methodsmentioning
confidence: 99%
“…In men with diabetes and depression, a significantly higher prevalence of ED is observed [ 60 , 134 ], with depressive symptoms showing an independent and positive association with the severity of ED [ 135 ]. Moreover, it has been demonstrated that young people in the early stages of psychosis have higher rates of ED [ 136 ] and that men suffering from bipolar disorder and post-traumatic stress disorder may also have a higher risk of ED [ 137 , 138 ], not associated with the use of psychotropic medications.…”
Section: Methodsmentioning
confidence: 99%
“…The most frequent of these is childhood sexual abuse, reported by 40-71% of patients linked to the severity of the abuse itself (Shearer et al, 1990;Paris et al, 1994;Zanarini et al, 2002). Consistent evidence show as sexual abuse during childhood is a reliable predictor of chronic PTSD (Müller et al, 2018), is strongly linked to ultra-high risk of psychosis (UHR), first -episode psychosis (FEP; Ciocca et al, 2021). Sexual trauma is particularly relevant for the development of addiction (Poppa et al, 2019) and it is often associated with the ineffectiveness of pharmacological treatment of anxiety disorders (Kim et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Psychometric scales are scientifically and clinically relevant tools used by physicians and psychologists to quantitatively assess patients’ sexual health 1 2 3 by means of patient-reported outcomes (PROs). 4 Male sexual function can be assessed by several psychometric scales: the 6-item International Index for Erectile Function (IIEF-6), the Erection Hardness Scale (EHS), and the Masturbation Erection Index (MEI) can be used to assess aspects related to erectile function; moreover, the Premature Ejaculation Diagnostic Tool (PEDT) can be used to assess the presence of premature ejaculation (PE) and its clinical consequences.…”
Section: Introductionmentioning
confidence: 99%